2020
DOI: 10.1177/0333102420977106
|View full text |Cite
|
Sign up to set email alerts
|

Interictal amylin levels in chronic migraine patients: A case-control study

Abstract: Background Recently, amylin and its receptors were found in different structures involved in migraine pathophysiology. Here, we evaluate interictal concentrations of amylin and calcitonin gene-related peptide in peripheral blood as biomarkers for chronic migraine. Methods We prospectively recruited patients with episodic migraine, chronic migraine and healthy controls. Interictal amylin and calcitonin gene-related peptide levels were assessed in blood samples using enzyme linked immunosorbent assay. Results We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…CGRP concentrations are reportedly elevated in the plasma, synovial fluid and CSF across a range of painful conditions: from tumourassociated pain to chronic lower back pain (Schou et al, 2017). This is consistent with migraine patients, where elevated plasma CGRP-LI has been observed during acute migraine attacks and in chronic migraine patients compared with healthy controls (Goadsby et al, 1990;Irimia et al, 2020). Interestingly, this elevation has been reported for up to 3 days following an acute migraine attack, suggesting sustained CGRP transcription and synthesis and/or release (Durham, 2006).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…CGRP concentrations are reportedly elevated in the plasma, synovial fluid and CSF across a range of painful conditions: from tumourassociated pain to chronic lower back pain (Schou et al, 2017). This is consistent with migraine patients, where elevated plasma CGRP-LI has been observed during acute migraine attacks and in chronic migraine patients compared with healthy controls (Goadsby et al, 1990;Irimia et al, 2020). Interestingly, this elevation has been reported for up to 3 days following an acute migraine attack, suggesting sustained CGRP transcription and synthesis and/or release (Durham, 2006).…”
supporting
confidence: 52%
“…Although the role of amylin in pain disorders is not well understood, studies examining amylin in primary headache disorders suggest a potential pro-nociceptive role for this peptide. In patients suffering from chronic, and to a lesser extent episodic, migraine displayed an elevated concentration of circulating amylin-LI, measured by ELISA, relative to non-migraineurs (Irimia et al, 2020). This elevation was independent of an individual's metabolic status and obesity.…”
Section: Overview and Contribution Of Amylin To Migraine And Painmentioning
confidence: 90%
“…The most likely mechanisms are through activation of amylin‐responsive receptors in the peripheral sensory neurons, 40 the circumventricular organs, or within the brain, although the amounts of amylin that cross the blood–brain barrier are very small 41–43 . A recent study reported that amylin levels were higher in chronic migraine patients compared to episodic migraine patients 44 . At present, it is unknown whether plasma amylin is increased during spontaneous migraine attacks.…”
Section: Discussionmentioning
confidence: 99%
“…In the periphery, the nociceptive fibers from TG neurons innervate the meninges, dural blood vessels, middle meningeal artery, and large cerebral arteries. Activation and sensitization of these peripheral structures occurs by the local release of vasoactive peptides, such as calcitonin gene-related peptide (CGRP), amylin, substance P and pituitary adenylate cyclase-activating peptide (PACAP) (49)(50)(51)(52), and inflammatory mediators (49). Sensitization of peripheral afferent TG fibers, or peripheral sensitization, explains the characteristic throbbing pain that worsens with physical activity during migraine attacks (49).…”
Section: Pathophysiology Of Allodynia In Migrainementioning
confidence: 99%